2009
DOI: 10.1002/eqe.960
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional vibration control of high‐tech facilities against earthquakes and microvibration using hybrid platform

Abstract: High-tech equipments engaged in the production of ultra-precision products have very stringent vibration criteria for their functionality in normal operation conditions and their safety during an earthquake. Most previous investigations were based on simplified planar models of building structures, despite the fact that real ground motions and structures are always three-dimensional. This paper hence presents a threedimensional analytical study of a hybrid platform on which high-tech equipments are mounted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Te hybrid control platform consisted of active hydraulic actuators and passive mounts with springs and dashpots between the platform and building. Numerical results demonstrated that the vibration of the passive control platform may exceed VC-B, whereas that of the hybrid-controlled platform could be efectively suppressed to meet VC-E. Hong et al [9] constructed a three-dimensional fnite element building model with a hybrid platform subjected to three-dimensional ground excitations. Te hybrid platform mounted on the second foor of the building consisted of several pairs of passive devices and active actuators.…”
Section: Introductionmentioning
confidence: 99%
“…Te hybrid control platform consisted of active hydraulic actuators and passive mounts with springs and dashpots between the platform and building. Numerical results demonstrated that the vibration of the passive control platform may exceed VC-B, whereas that of the hybrid-controlled platform could be efectively suppressed to meet VC-E. Hong et al [9] constructed a three-dimensional fnite element building model with a hybrid platform subjected to three-dimensional ground excitations. Te hybrid platform mounted on the second foor of the building consisted of several pairs of passive devices and active actuators.…”
Section: Introductionmentioning
confidence: 99%
“…al. [11] presented a three-dimensional analytical study of a hybrid platform on which high-tech equipments are mounted for their vibration mitigation. The literatures mentioned above have proven that small, customized viscous dampers are effective means of reducing the unwanted vibration of objects or building content.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, micro‐vibration has been intensively studied in concerns of human comfort and production yield for office buildings, biotechnology or metrology labs, and semiconductor fabs 4–16. Vibration control for sensitive equipment by using isolation devices or active control systems 14–25 has also been widely explored.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, micro-vibration has been intensively studied in concerns of human comfort and production yield for office buildings, biotechnology or metrology labs, and semiconductor fabs [4][5][6][7][8][9][10][11][12][13][14][15][16]. Vibration control for sensitive equipment by using isolation devices or active control systems [14][15][16][17][18][19][20][21][22][23][24][25] has also been widely explored. Figure 2 illustrates a typical double-fab TFT-LCD building that was piled up with two clean rooms and the supporting sub-fabs.…”
Section: Introductionmentioning
confidence: 99%